2015
DOI: 10.1177/1098612x15610683
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous asthenia (Ehlers–Danlos-like syndrome) of Burmese cats

Abstract: The clinical features of this genetic disease of Burmese cats are reviewed, especially in relation to the postulated 'vasculopathy' that gives rise to characteristic skin lesions. Long term management of this condition is discussed briefly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…Young age, clinical features, the SEI and histopathologic results in our case were well compatible with a congenital collagen defect. One study found histopathological features of feline cutaneous asthenia included alterations of collagen fibers in arrangement and length (i.e., shortening, disarray, curling, and uneven size) and disorganization of the collagen fibrils [2]. In this case of cat, similar histological findings were all clearly noticed.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Young age, clinical features, the SEI and histopathologic results in our case were well compatible with a congenital collagen defect. One study found histopathological features of feline cutaneous asthenia included alterations of collagen fibers in arrangement and length (i.e., shortening, disarray, curling, and uneven size) and disorganization of the collagen fibrils [2]. In this case of cat, similar histological findings were all clearly noticed.…”
supporting
confidence: 64%
“…Two forms of feline congenital cutaneous asthenia have been found [2]. In the autosomal dominant form of the disease, type I collagen was poorly packaged and thus it caused skin hyperextensibility and joint hypermobility in affected cats.…”
mentioning
confidence: 99%
“…The skin extensibility index, according to Hansen et al . (), was 27%. Some of the previous lacerations had slowly healed leaving shiny alopecic scars.…”
mentioning
confidence: 87%
“…More recently, EDS has also been observed in several Burmese cats and it was suggested that an autosomal recessive form of EDS may be segregating in this breed (Hansen et al . ).…”
mentioning
confidence: 97%
“…The Burmese is now one of the most genetically inbred cat populations worldwide, 3 and has been over-represented in a number of conditions, including frontonasal dysplasia (Burmese head defect), feline orofacial pain syndrome, 4 hypokalaemic polymyopathy, 5 diabetes mellitus, 6 , 7 cutaneous asthaenia, 8 endocardial fibroelastosis, 9 primary glaucoma 10 and GM2 gangliosidosis. 11 Genetic tests are available for GM2 gangliosidosis, 11 Burmese hypokalaemia 5 and Burmese head defect.…”
Section: Introductionmentioning
confidence: 99%